One night of sleep deprivation decreases treadmill endurance performance - Oliver, S. J.; Costa, R. J. S.; Laing, S. J.; Bilzon, J. L. J.; Walsh, N. P. (European Journal of Applied Physiology, 2009)
The aim was to test the hypothesis that one night of sleep deprivation will impair pre-loaded 30 min endurance performance and alter the cardio-respiratory, thermoregulatory and perceptual responses to exercise. Eleven males completed two randomised trials separated by 7 days: once after normal sleep (496 (18) min: CON) and once following 30 h without sleep (SDEP). After 30 h participants performed a 30 min pre-load at 60%VO2max VO2maxfollowed by a 30 min self-paced treadmill distance test. Speed, RPE, core temperature (T re), mean skin temperature (T sk), heart rate (HR) and respiratory parameters ( VO2 VO2,VCO2 VCO2, VE VE, RER pre-load only) were measured. Less distance (P = 0.016, d = 0.23) was covered in the distance test after SDEP (6037 (759) 95%CI 5527 to 6547 m) compared with CON (6224 (818) 95%CI 5674 to 6773 m). SDEP did not significantly alter T re at rest or thermoregulatory responses during the pre-load including heat storage (0.8°C) and T sk. With the exception of raised [(V)\dot]\textO2 VO2at 30 min on the pre-load, cardio-respiratory parameters, RPE and speed were not different between trials during the pre-load or distance test (distance test mean HR, CON 174 (12), SDEP 170 (13) beats/min: mean RPE, CON 14.8 (2.7), SDEP 14.9 (2.6)). In conclusion, one night of sleep deprivation decreased endurance performance with limited effect on pacing, cardio-respiratory or thermoregulatory function. Despite running less distance after sleep deprivation compared with control, participants` perception of effort was similar indicating that altered perception of effort may account for decreased endurance performance after a night without sleep.